Report from the Academic Conference “Entrepreneurship, Entrepreneurs and Enterprises: Between Synthesis and Case Study: On the 100th Anniversary of the Chair and Department of Economic History at the University of Poznań and the Adam Mickiewicz University” in Poznań on 22–23 September 2022 - Miłosz, Jan (Studia Historiae Oeconomicae, 2022)
On September 22–23, 2022, at the Collegium Historicum of the Adam Mickiewicz University in Poznań, an academic conference was held to celebrate the centenary of the Department of Economic History.